The Sensitivity of U.S. Inpayments and Outpayments to Real Exchange Rate Changes: Asymmetric Evidence From Africa. Issue 3 (3rd July 2019) - Bahmani-Oskooee, Mohsen; Arize, Augustine C.
ABSTRACT: A strand of the literature concentrates on assessing the impact of exchange rate changes on a country's inpayments from and outpayments to its trading partners. Most studies have considered the U.S. experience with partners from OECD but not for those from Africa. We fill this gap by including 14 African partners in our study. We assess not only the symmetric effects of exchange rate changes on the U.S. inpayments from and outpayments to each African partner, but also the asymmetric effects which requires incorporating nonlinear adjustment of the exchange rate. While we found asymmetric effects in the trade with almost all partners in the short run, in a limited number of cases the short-run effects lasted into long-run asymmetric effects. All in all, our findings are partner specific, but they provide more support for using nonlinear models.